Didactic resources used for teaching listening, and their contribution to english students - Alfaro Reyes, Martha Cecilia
One of the most important factors is the didactic resources that are used when teaching a second language. That is why the following research presents. The idea of developing this project was that the researchers noticed the lack of up-to- date didactic resources to improve the listening skill in the Foreign Languages Department.